2006
DOI: 10.1196/annals.1317.006
|View full text |Cite
|
Sign up to set email alerts
|

The Glucagon‐Like Peptides

Abstract: The glucagon-like peptides, GLP-1 and GLP-2, are cosecreted by intestinal L cells in response to nutrient ingestion. These peptides exert multiple effects on the gastrointestinal tract and pancreas to regulate the digestion, absorption, and assimilation of ingested nutrients, as well as providing feedback signals to the brain to modulate food intake. Tropic effects of GLP-1 and GLP-2 on their major peripheral target tissues, the beta cell and the intestinal epithelium, respectively, further enhance capacity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 126 publications
1
56
0
Order By: Relevance
“…GLP‐1 is secreted from intestinal L cells in response to ingestion of nutrients, including carbohydrate and lipids 5 . A previous study showed that alpha‐linolelic acid (α‐LA) promoted GLP‐1 secretion through the stimulation of G‐protein‐coupled receptor (GPR) 120, which is abundantly expressed in the intestine, in mice 6 .…”
Section: Introductionmentioning
confidence: 99%
“…GLP‐1 is secreted from intestinal L cells in response to ingestion of nutrients, including carbohydrate and lipids 5 . A previous study showed that alpha‐linolelic acid (α‐LA) promoted GLP‐1 secretion through the stimulation of G‐protein‐coupled receptor (GPR) 120, which is abundantly expressed in the intestine, in mice 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In the CNS the GLP2R is expressed in the hypothalamic nucleus, the hippocampus, the nucleus of the solitary tract, the parabrachial nucleus, the supramammillary nucleus, and the substantia nigra (Vrang & Larsen 2010). The main stimulus for the GLP2 release is represented by the presence of nutrients, specifically fats and carbohydrates, in the intestinal lumen (Brubaker 2006). After secretion, GLP2 is degraded by the enzyme dipeptidyl peptidase-IV (DPP-IV), which renders the peptide inactive by N-terminal truncation of the alanine at position 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The primary stimulus of incretin secretion is food consumption, in particular fat and carbohydrate. 7 The action of incretins is insulin dependent and ends when glucose levels are <55 mg/dL. 8 The effect of DPP4 inhibitors may be mediated via enhancement of GLP-1 secretion.…”
Section: Incretin Hormonesmentioning
confidence: 99%